Cultural participation and life satisfaction: an investigation across different family backgrounds - Romain Lerouge; Michela Arnaboldi (PLoS ONE, 2026)
The economic and social impact of cultural participation has recently become once more a subject of interest for policy-making, especially as a driver potentially affecting social inclusion and quality of life. Two topics of interest emerge in research on this subject. The first topic concerns the relationship between cultural experiences and life satisfaction, this being a comprehensive measure of the highest human motivation. The second topic relates to the multi-faceted relationship between cultural participation and family background. According to previous studies, these two topics are strictly intertwined; however, they have not been analysed in an integrated manner. Drawing on equality of opportunity theory, this study integrates both perspectives to provide a general overview on the link between cultural participation and life satisfaction for on people coming from different family backgrounds. Research based on a survey disseminated in Italy (N = 1 235) was conducted to investigate if and how family background moderates people’s ability to achieve life satisfaction through their involvement in cultural events. The results support customised policies that introduce a new approach to assessing the impact of cultural participation, thereby disclosing the role it plays in disadvantaged backgrounds and highlighting the cultural events responsible for the strongest benefits.